Calling all creeps! - Stine, R. L. (New York : Scholastic, 1996)
Ricky's plan to get revenge on Tasha for kicking him off the school paper backfires when the message he sneaks into the paper inviting creeps to call Tasha gets printed with his number instead and the calls he gets are from real Creeps--complete with scaly purple skin and long sharp fangs.
4.4
5-8
Keywords: Horror stories; Monsters -- Fiction; Schools -- Fiction; Horror fiction; Monsters -- Fiction; School stories